2006
DOI: 10.1111/j.1600-0765.2006.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Roxithromycin inhibits tumor necrosis factor‐α‐induced matrix metalloproteinase‐1 expression through regulating mitogen‐activated protein kinase phosphorylation and Ets‐1 expression

Abstract: Roxithromycin inhibits TNF-alpha-mediated MMP-1 induction through the downregulation of ERK1/2 and JNK activation and the subsequent reduction of Ets-1, suggesting that roxithromycin may have therapeutic use in periodontitis and other chronic inflammatory conditions involving MMP-1 induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…In addition, it significantly inhibits TNFalpha-induced c-Jun N-terminal kinase activation (JNP) and marginally inhibits extracellular signal-regulated kinase (ERK)1/2 activation, but not p38 mitogen-activated protein kinase activation. The inhibition of TNF-mediated VEGF and induction of Ets-1 suggest the potential therapeutic utility of RXM in chronic inflammatory conditions [81,82].…”
Section: Roxithromycinmentioning
confidence: 98%
“…In addition, it significantly inhibits TNFalpha-induced c-Jun N-terminal kinase activation (JNP) and marginally inhibits extracellular signal-regulated kinase (ERK)1/2 activation, but not p38 mitogen-activated protein kinase activation. The inhibition of TNF-mediated VEGF and induction of Ets-1 suggest the potential therapeutic utility of RXM in chronic inflammatory conditions [81,82].…”
Section: Roxithromycinmentioning
confidence: 98%
“…17 Previous studies demonstrated the stimulating effect of TNF-a on MMP and TIMP expression by gingival fibroblasts, periodontal ligament fibroblasts and osteoblasts. [17][18][19][20][21][22][23] It is unknown, however, whether cementoblasts respond to this cytokine.…”
Section: Introductionmentioning
confidence: 97%
“…RXM significantly inhibited TNFalpha-induced c-Jun N-terminal kinase activation (JNP) and marginally inhibited extracellular signal-regulated kinase (ERK) 1/2 activation, but not p38 mitogen-activated protein kinase activation. Furthermore, RXM reduced the induction of Ets-1, one of the critical factors in MMP-1 transcription [22]. The results of another study supported the antiinflammatory activities of AZM, since it was demonstrated that it reduced the levels of TNF-alpha and the inhibitions of NF-kappaB and specificity protein 1 (Sp1) DNA binding were proposed as possible mechanisms of this effect [23].…”
Section: Effects On Cytokines and Chemokinesmentioning
confidence: 81%